2020
DOI: 10.3390/s20082436
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on People Action Recognition in Social Robotics by Means of Common Spatial Patterns

Abstract: Action recognition in robotics is a research field that has gained momentum in recent years. In this work, a video activity recognition method is presented, which has the ultimate goal of endowing a robot with action recognition capabilities for a more natural social interaction. The application of Common Spatial Patterns (CSP), a signal processing approach widely used in electroencephalography (EEG), is presented in a novel manner to be used in activity recognition in videos taken by a humanoid robot. A seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Most authors consider it unnecessary to describe the computer hardware used [ 66 , 68 , 71 , 73 , 74 ]. However, in Table 2 , it can be observed that computer equipment with basic hardware has been used [ 63 ], as well as robots such as FACE [ 67 ], Robovie R3 [ 69 ], and Pepper [ 70 ].…”
Section: Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors consider it unnecessary to describe the computer hardware used [ 66 , 68 , 71 , 73 , 74 ]. However, in Table 2 , it can be observed that computer equipment with basic hardware has been used [ 63 ], as well as robots such as FACE [ 67 ], Robovie R3 [ 69 ], and Pepper [ 70 ].…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…Then, the HMM and ANN algorithms are combined to determine the body posture. Furthermore, Rodríguez et al [ 70 ] proposed an algorithm for the Pepper robot to recognize the actions (say hello, shake hands) that a person performed to improve human–robot interaction. Their proposal consists of implementing the Kinect sensor to extract the skeleton using the OpenPose and the HOG algorithms.…”
Section: Algorithms Used For the Bodymentioning
confidence: 99%
“…The method presented in this paper is a continuation of the work presented in [2], which uses CSP applied to skeleton information for video action recognition. In this work, an image is obtained for each video that summarizes the information of the video and that can be then classified using image classifiers.…”
Section: Proposed Approachmentioning
confidence: 99%
“…The approach presented herein continues with the work presented in [2], where Common Spatial Patterns (CSP), a method commonly used in Brain Computer Interface (BCI) for ElectroEncephaloGram (EEG) systems [3], [4], is used as feature extraction method for a video action recognition task.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation